“Producción de hojuelas dulces y saladas a partir de coco (cocos nuciferaL.) En la Región de San Martín - Infante Bravo, Jorge (1996)
This work is the development of coconut flakes Jl salty sweets using the hybrid - 121 (cocos nucifera l.) variety, its subsequent storage and transport. The samples obtained have the following characteristics: sweet pancakes; humidity 0.79%, fat 52.70%, proteins 6.10%, carbohydrates 35. 695), mineral 0.85%, fiber 3.87%; While the flakes salty presented the following composition: moisture or. HO ~ ~, fat 62.83%, proteins 6,78%, carbohydrates 22.27%, minerals 2. 30 ~ t, fiber 4. 92% reducing sugars no• presents in both samples. Was determined to do this the optimal parameters of flow of processing; control during and after the time of storage. The stages of the process involves the following operations: selection, pre-cooking, shell, mondado, washed, bleached, grated, pressed, first drying, preparation of solutions, mixing, second dried, cooled, packaged, stored and transport. In terms of the storage...